Exploiting full pomegranate potential for double benefit - Pal, Ram Krishna; Gaikwad, Nilesh N (Indian Horticulture, 2019)
Cultivation of pomegranate in India is increasing at a very rapid rate due to its high return on investment from a small piece of land in arid and semi-arid agro-ecosystem with severe scarcity of water. The fruit has wide acceptability among consumers because its edible part (arils) has attractive colour like that of brilliant Ruby stone filled with highly palatable sweet sour blend of juice with a small woody seed having proven nutraceutical value. Although, it is primarily a temperate crop yet it has been very well acclimatized in the tropical and sub-tropical parts of India. However, rapid growth of this crop may lead to market glut and farmers may not fetch the desired price of the harvested produce in future. The crop has potential to provide economic security to farming community and nutritional security to masses. Total utilization of pomegranate plays a crucial role to double the profitability of the farmers in view of expected fall in the price due to rapid rate of expansion in the area under cultivation and production in India. Growing health consciousness among the consumers and acquisition of its super fruit status has made marketing of pomegranate fruits and derived value-added product quite easy. Several opportunities of pomegranate based entrepreneurship development for doubling farmers’ income through processing and value-addition of pomegranate are discussed.